The Ethical Reflection on the Irreplaceability of Human Caregivers by Nursing Robots - Xinming DONG (Yixue yu zhexue)
Digital and disruptive technologies have significantly impacted the practice of medicine, with nursing field being a key area of impact. The application of nursing robots can effectively address occupational burnout among nurses and alleviate the burden of care caused by population aging. However, the development and application of nursing robots have faced some skepticism. In light of this controversy, this paper argues that, despite their notable advantages, nursing robots cannot fully replace human caregivers. Care ethics offer compelling evidence to support this view. In the future, the application of nursing robots will foster a new type of caregiver-patient relationship involving caregivers, robots, and patients. Consequently, there is a need to rethink and redefine the concept of quality care and to actively seek a new caregiving paradigm.